THE IMPLEMENTATION OF INTEGRATED CURRICULUM FOR EARLY EDUCATION (PAUD) IN MOJOKERTO DURING COVID-19 - Sutik, Sutik; Masitoh, Prof. Dr. Siti; Mariono, Dr. Andi (jfpublisher, 2022)
This research aims to describe the implementation of an integrated curriculum for early childhood education (PAUD) in Mojokerto during COVID-19 pandemic. This research design uses descriptive qualitative to describe the implementation of the integrated curriculum at Mojokerto Kindergarten Early Childhood School with research subjects at Al-Amin Kindergarten and Dharma Wanita Kindergarten Mojokerto East Java. This research uses the method or observation technique, in-depth interviews and documentation. This research uses an interactive model Miles & Huberman which is carried out through 3 stages; consist of (1) data reduction, (2) data display or data presentation, (3) conclusion drawing or data verification. Based on the research results, an integrated curriculum in early childhood is required to achieve learning objectives as an effort to develop children's characteristics and their way of thinking that observe everything holistically. By this integrated curriculum, students are expected to have the ability to identify, collect, assess and use information around them in meaningful way. The Implementation of an integrated curriculum during COVID-19 pandemic carried out via online and offline.